Reconstructing Racial Identity and the African Past in the Dominican Republic - Simmons, Kimberly Eison (Book collections on Project MUSE., 2009)
This book explores the socio-cultural shifts in the Dominican Republic's racial categories, concluding that Dominicans are slowly embracing blackness and ideas of African ancestry as they unbury the African past.